IMPLEMENTASI MODEL PEMBELAJARAN TEMATIK DAN KECERDASAN INTERPERSONAL TERHADAP HASIL BELAJAR IPA - Indah Kusumawati; M. Fahri Yasin (Akademika : Jurnal Teknologi Pendidikan, 2020)
The aims of this study was to find out the difference in Natural Science learning outcomes of students of elementary school class five taught by Thematic Model and Conventional Model, the interaction effect between Instructional Model and Interpersonal Intelligence on Natural Science learning outcomes, the difference in Natural Science learning outcomes of students with high and low interpersonal intelligence taught by instructional model with thematic model and conventional model. Design of research is an experimental method with the two-way analysis of variance (ANOVA) and the tukey analysis. The results showed 1) There was a significant difference where the Natural Science learning outcomes of grade V students who were taught thematic model were higher than students who were taught using conventional model. 2) There is an influence of learning model instruction with interpersonal intelligence on Natural Science learning outcomes of class V students. 3) Natural Science learning outcomes of class V students who have high interpersonal intelegence who are taught thematic model is higher than Natural Science learning outcomes of conventional model class’s V students taught conventional model. 4) Natural Science learning outcomes of class V students who have low interpersonal intelligence by being taught thematic model is lower compared to being taught using model conventional.